2017
DOI: 10.1007/s11892-017-0950-8
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption, Diabetes Risk, and Cardiovascular Disease Within Diabetes

Abstract: Men consume more alcohol than women in populations with and without diabetes. Light-to-moderate alcohol consumption decreases the incidence of diabetes in the majority of the studies, whereas heavy drinkers and binge drinkers are at increased risk for diabetes. Among people with diabetes, light-to-moderate alcohol consumption reduces risks of cardiovascular diseases and all-cause mortality. Alcohol consumption is less common among populations with diabetes compared to the general population. Moderate alcohol c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 98 publications
6
60
0
1
Order By: Relevance
“…At baseline, 61.8% of participants reported consuming alcohol in the past year, which is slightly less than the 70% of Americans from the general population . The overall quantity of alcohol consumed was low, consistent with previous findings that heavier drinking is less common among older adults compared with younger adults as well as those with diabetes relative to the general population . Further replication in younger samples and in people without diabetes is warranted.…”
Section: Discussionsupporting
confidence: 82%
“…At baseline, 61.8% of participants reported consuming alcohol in the past year, which is slightly less than the 70% of Americans from the general population . The overall quantity of alcohol consumed was low, consistent with previous findings that heavier drinking is less common among older adults compared with younger adults as well as those with diabetes relative to the general population . Further replication in younger samples and in people without diabetes is warranted.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the American Heart Association has acknowledged that consumption of 15 or more alcoholic beverages per week can increase blood pressure, obesity, stroke, breast cancer, suicide and accidents . In contrast, population research conducted over the last two decades indicates that alcohol consumption in moderation is associated with lower risk of cardiovascular disease and type 2 diabetes mellitus …”
Section: Introductionmentioning
confidence: 90%
“…5 In contrast, population research conducted over the last two decades indicates that alcohol consumption in moderation is associated with lower risk of cardiovascular disease and type 2 diabetes mellitus. 4,6,7 Periodontitis is a proinflammatory oral disease caused by the interaction of pathogenic bacteria and host response, resulting in attachment loss, which will lead to tooth loss. 8 Szabo et al in 1999 demonstrated that alcohol impairs T-cell function and neutrophil chemotaxis, which can alter immune responses, increasing the risk of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve (50%) out of the males in this study had given a history of alcohol consumption. As alcohol consumption alone is a risk factor for cardiovascular disease (20), our study sample male population is at high risk of cardiovascular disease.…”
Section: And Percentagesmentioning
confidence: 99%